Landscapes and social transformations on the Northwest coast : colonial encounters in the Fraser Valley - Oliver, Jeff, 1973- (Archaeology of colonialism in native North America., 2010)
The Fraser Valley in British Columbia has been viewed historically as a typical setting of Indigenous-white interaction. Jeff Oliver now reexamines the social history of this region from pre-contact to the violent upheavals of nineteenth and early twentieth century colonialism to argue that the dominant discourses of progress and colonialism often mask the real social and physical process of change that occurred here--change that can be more meaningfully tied to transformations in the land.